Cultural differences in processing online customer reviews: holistic versus analytic thinkers - Benedikt M. Brand; Cristopher Siegfried Kopplin; Theresa Maria Rausch (Electronic Markets, 2022)
While the majority of studies exploring online customer reviews in the light of intercultural comparisons draw on the theoretical framework of Hofstede's cultural dimensions, which faced justifiable criticism, we make use of Socio-Cognitive Systems Theory to illustrate how consumers from different cultures are cognitively processing information. By employing this alternative theory, it is shown that the (heretofore established) Elaboration Likelihood Model for examining online customer reviews does not serve as an applicable framework in intercultural contexts. Reviewing extant literature, we uncover incidents questioning the generalizability of previous studies on review credibility conducted among East Asians. Building upon a research model established at a national level, we interviewed Western (German; n=552) and East Asian (Chinese; n=585) consumers to analyze the intercultural appropriateness of the model. The results empirically validate the assumptions of the Socio-Cognitive Systems Theory, and thus, finds Chinese to perceive review credibility holistically, whereas Germans tend to categorize its antecedents for evaluating them separately.
Keywords: D11; D12; 620; Online customer reviews; Socio-Cognitive Systems Theory; Intercultural comparison; Elaboration Likelihood Model